Os efeitos do Game Design no processo de criação de jogos digitais utilizados no ensino de Química e Ciências: o que devemos considerar? - Guerreiro, Manoel Augusto da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Digital games can be inserted in the context of school education as tools to promote knowledge, favoring the playful learning, development of cognitive skills and also as a motivational resource in the classroom. These features have their greatest admirers among the young shool population. A teaching methodology, relatively new, proclain that it is possible to teach shool subjects using digital games in the process. It is the Digital Games Based Learning, advocated by many researchers in the field of cognitive science and game design. However, we know little about the process of construction of these digital media for the teaching of Chemistry and Sciences. Thus, this paper presents a proposal to create an educational digital games of Chemistry, under the two-dimensional perspective: the playful and educational. The objective of this research is to understand the importance of the aspects considered in order to assist in the process of creating digital games used for this purpose. Our methodology has a focus on building the game called Mr. Ratômico which addresses a school subject of chemistry discipline chosen according to criteria defined in this work. This subject matter was analyzd by two people - teachers and game designers, as these professionals are responsible for the teaching of chemistry and also the construction of digital games. Data were obtained from simi-structured questionnaires and analyzed from the perspective of mixed methodology, dueto to the qualitative and quantitative characteristics of the analysis of the game in question. The initial results obatined by the pilot test kit showed that the respondents of the two populations realized the aspects examined, found insconsistencies, suggested changes and indicated the most problematic aspects in the construction process of the game here analyzed. In further analysis to the settings shows, respondents identified the aspects analyzed and, in addition showed other than...

Jogos digitais podem ser inseridos no contexto do ensino escolar na forma de ferramentas de promoção do conhecimento, favorecimento da aprendizagem lúdica, desenvolvimento de habilidades cognitivas e, também, como recurso motivacional em sala de aula. Esses materiais encontram na população jovem escolar os seus maiores apreciadores. Uma metodologia de ensino, relativamente nova, apregoa que é possível ensinar conteúdos escolares utilizando jogos digitais nesse processo. É a Aprendizagem Baseada em Jogos Digitais, defendida por muitos pesquisadores da área da ciência cognitiva e do game design. Entretanto, pouco conhecemos sobre o processo de construção dessas mídias digitais para o ensino de Química e Ciências. Desta forma, este trabalho traz uma proposta para a criação de um jogo digital educativo de Química, sob a perspectiva de duas dimensões: a lúdica e a educativa. O objetivo desta pesquisa é entender a importância dos aspectos considerados, no intuito de colaborar com o processo de criação dos jogos digitais utilizados para esse fim. Nossa metodologia tem o enfoque na construção do jogo chamado Mr. Ratômico, que aborda um tema escolar da disciplina de Química escolhida segundo critério definidos neste trabalho. Esse objeto de estudo foi analisado por duas populações - os professores e os game designers, uma vez que esses profissionais são os responsáveis pelo ensino de Química e também pela construção de jogos digitais, respectivamente. Os dados foram obtidos a partir de questionários semi-estruturados e analisados sob a perspectiva da metodologia mista, devido às características qualitativas e quantitativas da análise do jogo em questão. Os resultados iniciais, obtidos pelo teste do jgo, demonstraram que os respondentes das duas populações perceberam os aspectos examinados, encontraram insconsistências, sugeriram alterações e indicaram os pontos mais problemáticos no processo de...
The effects of Game in Design in Digital Games creation process used in Chemistry and Science teaching: what should we consider?
Keywords: Quimica; Ensino; Jogos; Design; Chemistry